Innovative constituent of green economy formation (Eurasian Journal of Ecology, 2016)
Modern world faces serious economic, ecological and social problems. They are closely related with each other and require simultaneous solution. New paradigm of economic science – the theory of a green economy- has become an answer for challenges of the time. The theory bases on an approach that the economy is a part of the ecosystem, that is why its’ functioning mustn’t contradict to the laws of nature. This time task is to bring the economy to a harmony with an environment. Eco-innovations have to become a key element in this process. It is necessary to define what their peculiarities are and launch a mechanism of their creation and introduction.
Keywords: green economy; eco-innovations; sustainable growth; ecological problems